Nocturia, Sleep and Daytime Function in Stable Heart Failure - Redeker, Nancy S. (2012)
BACKGROUND: To evaluate nocturia severity and nocturia-related differences in sleep, daytime symptoms and functional performance among patients with stable heart failure (HF). METHOD & RESULTS: In this cross-sectional observational study we recruited 173 patients [M age = 60.3 ±16.8 years; n = 60 (35%) female; left ventricular ejection fraction M = 32 ±14.6] with stable chronic HF from HF disease management programs in the Northeastern United States. Participants reported nocturia and completed a Six Minute Walk test (6 MWT), one night of ambulatory polysomnography (PSG), and the Medical Outcomes Study SF 36, Epworth Sleepiness, Pittsburgh Sleep Quality Index, Multi-Dimensional Assessment of Fatigue, and the Centers for the Epidemiological Studies of Depression scales. Participants reported no (n = 30/17.3%), one or more (n = 87/50.2%), and three or more (n = 56/32.4%) nightly episodes of nocturia. There were decreases in sleep duration and efficiency, stages REM and 3–4 sleep, physical function, and 6 MWT distance; and increases in the percent wake after sleep onset, insomnia symptoms, fatigue and sleepiness across levels of nocturia severity. CONCLUSIONS: Nocturia is common, severe, and closely associated with decrements in sleep and functional performance and increases in fatigue and sleepiness in patients with stable HF.